In-vitro evaluation of antidiabetic and antioxidant activities of lime juice extract of Gossypium herbaceum leaves (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Management of diabetes mellitus increasingly focuses on controlling postprandial hyperglycemia through inhibition of carbohydrate-hydrolyzing enzymes responsible for gastrointestinal glucose release and absorption. This study evaluated the in vitro antidiabetic and antioxidant activities of a lime juice extract derived from Gossypium herbaceum leaves. Fresh leaves were extracted using lime juice (Citrus aurantifolia) as a natural solvent medium. Inhibitory activities against α-amylase and α-glucosidase were assessed alongside antioxidant capacity using DPPH, ABTS, and hydroxyl radical scavenging assays at concentrations of 7.8125–1000 μg/mL, conducted in triplicate using standard spectrophotometric protocols. Acarbose served as the reference enzyme inhibitor, while butylated hydroxytoluene (BHT) was used as the antioxidant standard. The extract exhibited concentration-dependent inhibition of both carbohydrate-digesting enzymes and significant free radical scavenging activity. Although reference standards demonstrated higher activity across most concentrations, ABTS radical scavenging increased progressively with dose, approaching BHT performance at higher concentrations. Notably, hydroxyl radical scavenging at 31.25 μg/mL showed no significant difference from BHT, indicating strong antioxidant potential at moderate dosage. In contrast, α-glucosidase inhibition remained significantly lower than acarbose (p < 0.05) at all tested concentrations, suggesting moderate regulation of carbohydrate digestion rather than complete enzyme suppression. These findings demonstrate that lime-mediated extraction of Gossypium herbaceum leaves yields appreciable hypoglycemic potential through partial enzyme inhibition combined with enhanced antioxidant defense mechanisms. Synergistic contributions from ascorbic acid and bioactive phytochemicals present in Citrus aurantifolia likely underpin the observed bioactivity. Overall, the extract represents a promising natural candidate for development as an oral antidiabetic phytomedicine aimed at complementary diabetes management.